Sexism, English and Yoruba - Yusuf, Yisa Kehinde (Linguistik Online, 2002)
This paper surveys the incidence of sexism in the structure and use of English, and compares it with corresponding aspects of Yoruba. Subsequently, it examines the areas in which, due to the co-existence of the two languages in southwestern Nigeria, the languages influence one another with regard to sexism. The paper shows that while Yoruba is not sexist in some respects in which English is, English imposes sexism on the language. It shows also areas in which sexism existing independently in both languages reinforce one another. Finally, it shows how sexism in Standard English seems to have been eliminated in the formation of Nigerian Pidgin English which derives from the contact between English and Yoruba.